Characterization of Antineoplastic Agents Inducing Taste and Smell Disorders Using the FAERS Database - Risa Hamazaki; Yoshihiro Uesawa (MDPI AG, 2024)
Taste and smell disorders can worsen the nutritional status of patients receiving chemotherapy and potentially affect drug treatment. However, there is limited knowledge on antineoplastic agents that induce taste and smell disorders. Therefore, we used the U.S. Food and Drug Administration Adverse Event Reporting System database to analyze the characteristics of patients and antineoplastic agents in relation to taste and smell disorders. No gender differences related to the onset of taste and smell disorders were found, whereas older age was identified as a possible risk factor. Among the antineoplastic agent classes, protein kinase inhibitors appeared to be particularly likely to induce taste and smell disorders. According to the cluster and principal component analyses, antineoplastic agents were deemed to induce taste or smell disorders. In addition, antineoplastic agents that decreased or changed these sensations could be classified. These findings might be useful in selecting drugs for patients experiencing similar side effects.